Development of torus-shaped elastic body as a vibration absorber for flexural vibration in railway vehicle carbody and its experimental validation using commuter-type vehicle - Takahiro TOMIOKA (The Japan Society of Mechanical Engineers, 2017)
This paper presents a study to reduce flexural vibrations of rail vehicle carbody, which have large impact on ride quality, by utilizing deformation of an elastic body as a dynamic vibration absorber (DVA). Donut-shape (called "torus" in this study) is proposed as the elastic body considering practical application to rail vehicles. A numerical model to design an elastic torus using finite element (FE) analysis was developed, and it has been demonstrated that the shape and the size of a torus can be determined so as to have desired natural frequency by the FE model. A torus dedicated to a DVA for rail vehicles made of rubber filled with water was designed and manufactured actually. In order to validate the DVA effect of the water-filled elastic torus, a series of stationary vibration tests using a commuter-type test vehicle with stainless steel carbody was conducted. Since the tested vehicle showed two peaks on the frequency response function (FRF) measured on the floor and both of them should be reduced simultaneously to improve ride quality of the vehicle, the authors applied the elastic torus as "double-decker" style (stack a torus up on another torus). Both of the peaks were successfully reduced by applying the double-decker elastic torus. It has been confirmed that the multi-modal vibration reduction effect was achieved because a set of double-decker torus act like a two-degrees-of-freedom (2-DOF) system. Influence on the vibration reduction effect by the difference of the number of applied tori and their distribution on the floor were investigated.